Synaptic Loss in Alzheimer's Disease: Mechanistic Insights Provided by Two-Photon in vivo Imaging of Transgenic Mouse Models - Subramanian, Jaichandar; Savage, Julie C.; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2020)
Synapse loss is the strongest correlate for cognitive decline in Alzheimer’s disease. The mechanisms underlying synapse loss have been extensively investigated using mouse models expressing genes with human familial Alzheimer’s disease mutations. In this review, we summarize how multiphoton in vivo imaging has improved our understanding of synapse loss mechanisms associated with excessive amyloid in the living animal brain. We also discuss evidence obtained from these imaging studies for the role of cell-intrinsic calcium dyshomeostasis and cell-extrinsic activities of microglia, which are the immune cells of the brain, in mediating synapse loss.